(1)(x^2/x)-y-x-y(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)

来源:学生作业帮助网 编辑:作业帮 时间:2024/06/22 08:58:00
(1)(x^2/x)-y-x-y(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)

(1)(x^2/x)-y-x-y(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)
(1)(x^2/x)-y-x-y
(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)

(1)(x^2/x)-y-x-y(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)
(1)x^2/x)-y-x-y
=x-y-x-y
=-2y
(2)(a/a-b)-(a/a+b)-(2b^2/a^2-b^2)
=a(a+b-a+b)/(a^2-b^2)-(2b^2/a^2-b^2)
=2b/(a+b)

第一题不是等于2y吧
^ 是什么意思?

(1) -2y

(1)(x^2/x)-y-x-y
=x-x-2y
+-2y
(2)(a/a-b)-(a/a+b)-(2b^2/a^-b^2)
=2b/(a+b)
楼主有时间上网提问不如好好练习